Comparative bio-efficacy of nuclear polyhedrosis virus (NPV) and Spinosad against American bollwormm, Helicoverpa armigera (Hubner) - Nawaz,Ahmad (2019)
ABSTRACT American bollworm (ABW), Helicoverpa armigera (Hubner), is considered as a major pest of cotton, Gossypium hirsutum, all over the globe. Due to its destructive feeding nature and continuous consumption of the same chemicals, it devolved resistant against many insecticides. Therefore, a combined application of bio- and synthetic-pesticide need to evaluate against this pest. The entomopathogenic viruses like nuclear polyhedrosis virus (NPV), a member of baculoviruses, can be the potential candidates for better control against ABW. The present study was conducted to assess the comparative efficacy of NPV and Spinosad 240SC (with the concentration of 250 mL · ha-1) against ABW in the controlled environment. The ABW was treated with different concentrations of NPV and Spinosad separately and in a combination of NPV with 0.1% Spinosad. The results revealed that highest concentrations showed highest mortality (95%) followed by 95%, 92%, 84%, 82% and 78% mortality at 1 × 109, 1 × 108, 1 × 107, 1 × 106 and 1 × 105 POBs, respectively. Spinosad when mixed in diet give 100% mortality at 0.8% followed by 50.87%, 42.10%, 29.82%, 26.31% and 22.80% mortality at 0.4%, 0.2%, 0.1%, 0.5% and 0.025% respectively. The results of this study revealed that microbial control of ABW through NPV is an effective tool. The repeated use of synthetic pesticides caused the resurgence of many insect pests, and this study results would provide useful insight to build a framework for future investigations for the management of many major insect pests.